Pendampingan Pembuatan Akun Sinta Dosen Homebase STIT Hidayatullah Batam - Frangky Silitonga; Mohammad Ramli; M Muthma'innah (SIGMA : Jurnal Sinergi Mengabdi, 2023)
In this community service and management training activity for the management of the Sinta Lecturer Account at the STIT. Hidayatullah Batam Kepulauan Riau College of Science, this is part of the collaboration service activity between the Batam Tourism Polytechnic and STIT. Hidayatullah Batam Kepulauan Riau. The target achievement of this activity is to register all of the Lecturer's accounts that are homed at STIT. Hidayatullah Batam Kepulauan Riau. In collaboration service activities between STIT. Hidayatullah Batam Kepulauan Riau. Hidayatullah Batam Riau Archipelago with the Batam Tourism Polytechnic, the method of community service activities is carried out face to face using a practical approach is preferred, while the lecture method as support for accelerating understanding during the training and mentoring process. The method approach used is lectures, role play and demonstrative as well as direct hands-on practice that has been scheduled regularly and structured. The results obtained were that participants were able to register their respective Sinta accounts as lecturers and were able to synchronize GS, Garuda, WoS and Scopus Id accounts for those who already had them. Activate all Sinta Lecturer accounts at STIT. Hidayatullah Batam Kepulauan Riau is also getting better, which so far has not been well exposed, especially for prospective students who will register to gain knowledge at STIT. Hidayatullah Batam Kepulauan Riau. The limitations of varying laptop specifications, time and instruments used during the assistance activities of this community service activity can be minimized with the support of internet access technology which is quite good and the enthusiasm of the activity participants and a family atmosphere to jointly advance STIT. Hidayatullah Batam Kepulauan Riau. In the end all lecturers can see the sinta index in the last 3 years of the institution's sinta order.